Proprietary estoppel and property rights - Bright, S; McFarlane, B (Cambridge University Press, 2005)
This article focuses on a particular aspect of the operation of proprietary estoppel: it asks when a proprietary estoppel claim will give rise to a property right. The inquiry proceeds on the linked assumptions that proprietary estoppel is a means of acquiring rights and that rights thereby arising take effect immediately, without the need for any court order. Like any other means of acquiring rights, proprietary estoppel can give rise either to personal rights or to property rights: in some cases the estoppel claimant is acknowledged to have a personal right (e.g. to damages or a licence to use land); in others a property right (e.g. a lien; an easement; a lease; or a freehold). The central argument of this article is that proprietary estoppel should give rise to a property right only if that is necessary to protect the claimant's reasonable reliance. Where a personal right gives sufficient protection that will have to do, whatever the claimant may have been promised or expected; this may well mean that the circumstances in which a property right arises are more narrow than has been thought.